Developing Guided Discovery Learning-Based Neurodroid Learning Media for Critical Thinking Skills - Lestari, Amelia; Lisanti, Elsa; Ristanto, Rizhal Hendi (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aimed to develop guided discovery learning-based android learning media to improve critical thinking skills. The developed biology learning media was applied to the nervous system material. The discussion of the physiology of the nervous system is one of the difficult biological materials to understand because it includes the organization and structure of neurons and their functions, ion pump mechanisms when neurons are at rest, action potential mechanisms, mechanisms for neurons to communicate with other cells in the synapses, and organization of the nervous system. This study used research and development (R&D) with a method developed by Thiagarajan, namely the 4D model with stages: define, design, develop and disseminate. The stages of this study are limited to the development stage. The results showed that the media was feasible with media, language, and a material expert validation of 3.5, 3.8, and 3.3, respectively.